(untitled) (World Science, 2018)
The beginning of development of Kazakhstani business education dates back to the end of the 80s – beginning of the 90s of the XX century. Along with the achievements in the sphere of business education, there are key issues that hampers the development of business schools and have an impact on the learning outcomes and the quality of business education in general. This article reviews the stages of development of business education in Kazakhstan and explores key issues in this sphere. Furthermore, the author suggests a series of systematic measures to strengthen the capacity of business education in Kazakhstan and gives the examples of contribution of Almaty Management University in this sphere.